Enhancing Green Food Intention and Creativity Through Problem-Based Learning Integrated with Scaffolded Nutrition among Pre-Service Science Teachers - Annisa Nur Khasanah; Dadan Rosana; Insih Wilujeng; Arifin Septiyanto; Muhammad Nur Hudha; Rofiqul Umam (Universitas Negeri Semarang, 2026)
This study aims to determine the effect of the implementation of Problem-Based Learning through Scaffolded Nutrition (PBL-SN) on increasing green food intention and creativity in pre-service science teachers to support SDGs, the effect of the implementation of PBL-SN in developing creativity in the context of sustainable food consumption in pre-service science teachers, and whether there is a significant relationship between green food intention and creativity of pre-service science teachers after participating in PBL-SN based learning. The novelty of the research lies in integrating PBL with Scaffolded Nutrition as a specific instrument to simultaneously increase Creativity and Green Food Intention among pre-service science teachers, thereby supporting SDGs 2, 3, and 12. This study is a quantitative, quasi-experimental, posttest-only research design. The statistical tests used are t-tests and multiple linear regression. The results of this study show that the green food intention variable has an average EC (M = 3.47) and CC (M = 3.27), with t = -1.841 and Cohen's d = 0.516, indicating a moderate effect. The creativity variable shows that the average EC (M = 87.52) is higher than the average CC (M = 82.76), with t = -4.078 and Cohen's d = 1.141; the effect size is relatively large, indicating that the treatment given to the EC has a strong impact on increasing the creativity of pre-service science teachers. There is a weak positive correlation between creativity and green food intention, suggesting no strong relationship between the two variables in the intervention group.